PENGUJIAN KONDISI ISOLASI MAIN TRANSFORMATOR GTG 1.1 DENGAN METODE DIELECTRIC RESPONSE ANALYSIS (DIRANA) - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
One Way to Maintain reliability review namely with a transformer maintenance how to operate good. transformer maintenance operations can be done online or hearts operational state and operates offline or exit network. Operates offline transformer testing can be done with condition assessment method used to review assessing the costs kos transformer. Testing DIRANA (Dielectric Response Analysis) is a prayer one condition assessment method for isolation of review helps predict conditions like oil conductivity and moisture content of the paper on country isolation transformer. Writing tests DIRANA singers perform, so that can be give the next follow-up recommendations should taken against the main transformer at PLTGU. On moisture testing method CHL dry category because value <2.2%, thus by Main Transformer (MT) 1.1 GT hearts normal conditions. Transformer oil conductivity values From the findings of Measurement worth 290 fs / m, the value of the conductivity of the transformer oil SIGN categories Good hearts.